Earnings Predictability And Broker-Analysts’ Earnings Forecast Bias - Eames, Michael; Glover, Steven (Journal of Applied Business Research, 2017)
Scholars have reasoned that analysts issue optimistic forecasts to improve their access to managers’ private information when earnings are unpredictable. While this requires a managerial preference for analyst forecast optimism, the observed walk-down of analyst expectations to beatable forecasts is consistent with a managerial preference for pessimism in short-horizon forecasts. Using data from various sample periods, alternative model specifications, and various measures of earnings unpredictability, we find that pessimism, not optimism, in short-horizon forecasts is associated with increasingly unpredictable earnings. Our results suggest that firms can more effectively manage analysts’ earnings expectations downward when earnings are relatively unpredictable.
Keywords: Earnings Predictability; Earnings Forecast Bias